2010
DOI: 10.1074/jbc.m110.121061
|View full text |Cite|
|
Sign up to set email alerts
|

Crotepoxide Chemosensitizes Tumor Cells through Inhibition of Expression of Proliferation, Invasion, and Angiogenic Proteins Linked to Proinflammatory Pathway

Abstract: Crotepoxide (a substituted cyclohexane diepoxide), isolated from Kaempferia pulchra (peacock ginger), although linked to antitumor and anti-inflammatory activities, the mechanism by which it exhibits these activities, is not yet understood. Because nuclear factor B (NF-B) plays a critical role in these signaling pathways, we investigated the effects of crotepoxide on NF-B-mediated cellular responses in human cancer cells. We found that crotepoxide potentiated tumor necrosis factor (TNF), and chemotherapeutic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Also, the transcription factor Snail translocates into the nucleus in metastatic human cancer [35]. In the current study, we found that [6]-gingerol inhibited the nuclear translocation of Snail, which is regulated by NF- κ B. Inhibition of Snail and MMP-9 could be the mechanism of [6]-gingerol-induced inhibition of cancer cell metastasis.…”
Section: Discussionmentioning
confidence: 51%
“…Also, the transcription factor Snail translocates into the nucleus in metastatic human cancer [35]. In the current study, we found that [6]-gingerol inhibited the nuclear translocation of Snail, which is regulated by NF- κ B. Inhibition of Snail and MMP-9 could be the mechanism of [6]-gingerol-induced inhibition of cancer cell metastasis.…”
Section: Discussionmentioning
confidence: 51%
“…In this study, 3-FC inhibited constitutive NF-B activation, a critical element in the survival and proliferation of various tumor cell types (35). The inhibition of NF-B activation by 3-FC was specific, as it failed to inhibit Oct-1 activation.…”
Section: Discussionmentioning
confidence: 88%
“…The protein was prepared using the default parameters of the protein preparation workflow in the Schrödinger suite. The docking grid was centered around Arg 33 , Arg 35 , Tyr 36 , Glu 39 , and Arg 187 , as they were deemed critical for ligand and DNA binding (22).…”
Section: Assay For Nf-b-dependent Reporter Gene Expression-tomentioning
confidence: 99%
“…This NF-κB suppression leads to the down-regulation of its regulated gene products, including COX-2, MMP-9 and cyclin D1. Nutraceuticals derived from various kinds of ginger, such as crotepoxide [30], zerumbone [31], 1′-acetoxychavicol acetate [32] and [6]-gingerol [33], have been reported to suppress the NF-κB signalling pathway and induce apoptosis in a variety of human cancer cell lines. Recently, zerumbone has been shown to suppress the receptor activator of NF-κB ligand (RANKL)-induced NF-κB activation and osteoclastogenesis induced by RANKL and tumour cells, thus decreasing osteolysis in MDA-MB-231 breast cancer tumour-bearing athymic nude mice [34].…”
Section: Transcription Factors As a Link Between Diet And Cancermentioning
confidence: 99%